Dimensi Relasional Filosofi Kuni Agu Kalo dalam Masyarakat Manggarai - Denar, Benediktus; Seran, Florensia Imelda; Jewadut, Jean Loustar (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
This article aims to introduce a paradigm of life which is a guide and guide for the lives of the Manggarai-NTT people. For them, building relationships with others, the natural environment, and the Creator is one of the requirements for their existence as human beings. This is clearly seen in the ancient philosophy of kuni agu kalo. However, amid the pressure of progress and modernization, the implementation of the ancient philosophy of kuni agu kalo in the conduct of daily life is increasingly eroded. This is reflected in the fact that the culture of hatred and violence is getting stronger due to economic motives, social jealousy, and politics. In addition, the destruction of the environment is becoming increasingly massive. This research uses a qualitative approach with ethnographic methods. The results of this research show that the kuni agu kalo philosophy can be a philosophical basis for the Manggarai people to build relationality towards each other, the environment, and towards the highest being. For this reason, this philosophy needs to be maintained but also needs to be implemented in daily life practices to create better public civility.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//